Integrating Green Management in Islamic Educational Institutions: Strategies for Sustainable Education - Kusnan, Kusnan; Daeng Pawero, Abdul Muis Vangino; Ismail, Feiby (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study aims to analyze the integration of green management practices in Islamic educational institutions by exploring their implementation models, challenges, and contributions to the creation of environmentally sustainable learning environments. The novelty of this Research lies in its focused synthesis of green management principles with Islamic ethics as an area that remains underexplored, especially within madrasas and Islamic boarding schools. Using a qualitative systematic literature review, this study examines environmentally friendly facility management, resource conservation initiatives, and programs designed to cultivate ecological awareness and responsibility among students. The results indicate that applying green management leads to concrete improvements, including increased energy and water efficiency, reduced waste generation, and cleaner, more orderly school environments. Beyond operational benefits, green practices also play a significant educational role by shaping students' ecological character through values such as cleanliness (ṭahārah), simplicity (basāṭah), and stewardship (khilāfah) over nature as mandated in Islamic teachings. However, challenges remain, particularly in institutional policy consistency, limited adoption of green technologies, and insufficient community engagement. This study underscores the need for strengthened institutional policies, teacher capacity-building, and broader collaboration with external partners to sustain green management initiatives in Islamic schools.